2020
DOI: 10.1161/circulationaha.119.044320
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations and Decreased Expression of the Epigenetic Regulator TET2 in Pulmonary Arterial Hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is a lethal vasculopathy. Hereditary cases are associated with germline mutations in BMPR2 and 16 other genes. However, these mutations occur in under 25% of idiopathic PAH patients (IPAH) and are rare in PAH associated with connective tissue diseases (APAH). Preclinical studies suggest epigenetic dysregulation, including altered DNA methylation, promotes PAH. Somatic mutations of Tet-methylcytosine-dioxygenase-2 (TET2), a key enzyme in DNA demethylation, occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 54 publications
8
116
2
1
Order By: Relevance
“…In agreement with these experimental findings, it has been reported that individuals that harbour TET2mediated clonal haematopoiesis exhibit significantly higher serum levels of IL-1b and IL-6 in the TOPMed cohort [30]. Finally, a recent study reported that rare germline variants in TET2 may contribute to pulmonary arterial hypertension via an IL-1b-dependent mechanism [31].…”
Section: Mechanistic Links Between Clonal Haematopoiesis and Cardiovasupporting
confidence: 67%
“…In agreement with these experimental findings, it has been reported that individuals that harbour TET2mediated clonal haematopoiesis exhibit significantly higher serum levels of IL-1b and IL-6 in the TOPMed cohort [30]. Finally, a recent study reported that rare germline variants in TET2 may contribute to pulmonary arterial hypertension via an IL-1b-dependent mechanism [31].…”
Section: Mechanistic Links Between Clonal Haematopoiesis and Cardiovasupporting
confidence: 67%
“…We and others have recently proposed that DNA methylation and other epigenetic modifications potentially promote maladaptive gene expression, a determinant of inflammatory and hyperproliferative cell phenotype, in remodeled PA (Hu et al, 2019;Joshi et al, 2020;Potus et al, 2020). Furthermore, we recently showed that expression of Tet2, a DNA demethylase considered as a master regulator of differentiated fate of SMC This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study showed diminished TET2 in peripheral blood cells of PAH patients, which engenders the epigenetic link of DNA demethylation to PAH progression ( 16 ). However, DNA methylation regulated by DNMTs and TETs is strain, species, organ, and stimuli dependent.…”
Section: Discussionmentioning
confidence: 99%